2018
DOI: 10.1111/jora.12382
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sensitivity to Parenting and Peer Environments: Early Temperament and Adolescent Externalizing Behavior

Abstract: Although parenting behavior and friendship quality predict adolescent externalizing behaviors (EBs), individual differences in temperament may differentially affect susceptibility to these factors over time. In a multi-method and multi-informant study of 141 children followed prospectively from toddlerhood to adolescence, we tested the independent and interactive associations of age 3 reactive temperament (e.g., negative emotionality) and age 13 observed parenting (i.e., positive and negative behavior) and fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…These findings are consistent with previous studies showing that the interaction of negative parenting with child temperament/personality traits generally follows a diathesis–stress pattern (Kiff et al, 2011 ; Meunier et al, 2011 ; Tung et al, 2019 ). Thus, children with higher impulsivity and irritability, lower effortful control, difficult temperaments or children higher in negative affectivity had a greater risk for adjustment problems in the context of negative parenting (Leve et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with previous studies showing that the interaction of negative parenting with child temperament/personality traits generally follows a diathesis–stress pattern (Kiff et al, 2011 ; Meunier et al, 2011 ; Tung et al, 2019 ). Thus, children with higher impulsivity and irritability, lower effortful control, difficult temperaments or children higher in negative affectivity had a greater risk for adjustment problems in the context of negative parenting (Leve et al, 2005 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is also important to recognize that some plasticity markers may confer differential susceptibility, that is, both risk and vantage sensitivity, whereas others may confer only vulnerability to risk, and still others may confer only vantage sensitivity (Pluess and Belsky, 2013 ). Previous studies have focused mainly on genotypes or temperament traits (Belsky and Pluess, 2009 ; Kiff et al, 2011 ; Slagt et al, 2016a ; Tung et al, 2019 ), whereas our study explores the role of child personality traits as potential moderators of parenting influence.…”
Section: Introductionmentioning
confidence: 99%
“…These findings reinforce the results of the studies that measured parental and peer environment in the same sample (Janssens et al., 2017; Tung et al., 2018). Those studies found individual differences in environmental sensitivity to some aspects of the environment (e.g., negative parenting) but not to others (e.g., friendship conflict), as expressed in some outcomes (e.g., rule‐breaking) but not others (e.g., aggressive behavior).…”
Section: Discussionsupporting
confidence: 87%
“…Adolescents who are sensitive to their parents are not necessarily sensitive to their peers As an attempt to examine domain-generality versus domain-specificity, we tested whether individuals perceiving themselves as highly sensitive to their parents also perceive themselves as highly sensitive to their peers. To our knowledge, only two previous studies in the literature on individual differences in environmental sensitivity have included measures of both the parental and peer environments in the same sample (Janssens et al, 2017;Tung et al, 2018). However, they did not directly assess whether the same individuals who demonstrated greater sensitivity to their parents were also more sensitive to their peers.…”
Section: 2mentioning
confidence: 99%
“…Secondly, in the literature, negative emotionality has been widely tested and found as a marker of differential susceptibility (Pluess & Belsky, 2010; Roisman et al, 2012; Slagt et al, 2016). In some studies, negative emotionality is measured by including items related to infants’ ability to soothe and recovery from distress (Vitaro et al, 2006; Paulussen‐Hoogeboom et al, 2008; Tung et al, 2019). Although the soothability subscale mostly covers items about whether the infant is soothed easily when there is a parental intervention, infants’ own ability to calm down without caregiver intervention might also be important, especially in the context of non‐parental care.…”
Section: Introductionmentioning
confidence: 99%